Patagonian Cypress (Austrocedrus chilensis): The Cedarwood of the Emblematic Architecture of North Patagonia - Aparicio, Alejandro Gabriel; Pastorino, Mario Juan (Springer, 2021)
The Patagonian cypress Austrocedrus chilensis (D. Don) Pic. Serm. & Bizzarri, also known as Chilean cedar, is a dioecious, anemophilous, and anemochorous conifer (Cupressaceae), native to Argentina and Chile. In Argentina, it grows along a ca. 60 km wide strip that extends parallel to the Cordillera de Los Andes, from 37° 07′ to 43° 44′ S (Pastorino et al. 2006), within the Mediterranean climatic zone of North Patagonia (Fig. 6.1). A recent study compiling information on areas with presence of cypress, from dense compact forests to patches with scattered, isolated trees, yielded a total of 262,422 ha, of which 41.78% are under the jurisdiction and protection of the National Parks Administration (Pastorino et al. 2015). One of the most remarkable auto-ecological aspects of the cypress is its occurrence across a severe west to east annual rainfall gradient that decreases from ca. 3000 to 400 mm or even less in the xeric eastern border of the species. In pure, compact forest patches, cypress averages 20–25 m in height, and we have measured individuals up to 44 m in certain highly productive stands. The average diameters in adult trees range between 30 and 40 cm, but individuals of more than 1 m can usually be found (Fig. 6.2). The boles are normally straight, somewhat conical, with a thin bark in young individuals and longitudinal cracks at maturity. The crowns are mostly pyramidal and compact.